2018
DOI: 10.1016/j.jvs.2018.03.408
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of early mortality and readmissions among dialysis patients undergoing lower extremity amputation

Abstract: Objective Patients receiving dialysis are at increased risk for lower extremity amputations and postoperative morbidity. Limited studies have examined differences in 30-day outcomes of mortality and healthcare use after amputation or the preoperative factors that relate to worsened outcomes in dialysis patients. Our objective was to examine dialysis-dependency and other preoperative factors associated with readmission and/or death after lower extremity amputation. Methods Retrospective cohort study of dialys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
3
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 33 publications
(30 reference statements)
1
24
3
5
Order By: Relevance
“…The definition of chronic dialysis varied across studies, with 22 studies using registry-based definitions, six using International Classification of Disease Coding (ICD) and the remaining studies confirming chronic dialysis status by medical chart reviews. Non-emergent cardiac surgery was the most commonly reported type of surgery (28%) [ 14 – 27 ], followed by general surgery (24%) [ 2 , 28 38 ], orthopaedic surgery (22%) [ 39 49 ], vascular surgery (16%) [ 50 56 ], and urologic/gynaecologic surgery (8%) [ 57 60 ]. Twenty-six of the 49 studies assessed a single surgical procedure [ 18 – 20 , 22 , 24 – 26 , 32 , 34 , 36 39 , 41 43 , 45 , 48 – 50 , 53 , 54 , 56 59 ], while the remaining 23 studies examined a mixture of discipline-specific surgical interventions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The definition of chronic dialysis varied across studies, with 22 studies using registry-based definitions, six using International Classification of Disease Coding (ICD) and the remaining studies confirming chronic dialysis status by medical chart reviews. Non-emergent cardiac surgery was the most commonly reported type of surgery (28%) [ 14 – 27 ], followed by general surgery (24%) [ 2 , 28 38 ], orthopaedic surgery (22%) [ 39 49 ], vascular surgery (16%) [ 50 56 ], and urologic/gynaecologic surgery (8%) [ 57 60 ]. Twenty-six of the 49 studies assessed a single surgical procedure [ 18 – 20 , 22 , 24 – 26 , 32 , 34 , 36 39 , 41 43 , 45 , 48 – 50 , 53 , 54 , 56 59 ], while the remaining 23 studies examined a mixture of discipline-specific surgical interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-three studies extracted information from existing data registries while the remaining extracted information from re-examined health records. Thirty-three studies were reported from North America [ 2 , 15 17 , 21 – 24 , 27 – 29 , 31 , 33 37 , 40 , 42 , 44 46 , 49 , 51 56 , 58 , 60 , 62 ], ten from Asia [ 18 – 20 , 26 , 30 , 38 , 39 , 43 , 47 , 48 , 50 , 59 ] and four from Europe [ 14 , 32 , 41 , 57 ]. Thirty-four studies were published after 2010 [ 2 , 14 , 16 , 22 – 24 , 27 – 31 , 33 , 34 , 36 50 , 53 56 , 58 60 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…The de nition of chronic dialysis varied across studies, with 22 studies using registry-based de nitions, six using International Classi cation of Disease Coding (ICD) and the remaining studies con rming chronic dialysis status by medical chart reviews. Non-emergent cardiac surgery was the most commonly reported type of surgery (28%)(14-27), followed by general surgery (24%) (2,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38), orthopaedic surgery (22%) (39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), vascular surgery (16%) (50)(51)(52)(53)(54)(55)(56), and urologic/gynaecologic surgery (8%) (57)(58)(59)(60). Twenty-six of the 49 studies assessed a single surgical procedure (18-20, 22, 24-26, 32, 34, 36-39, 41-43, 45, 48-50, 53, 54, 56-59), while the remaining 23 studies examined a mixture of discipline-speci c surgical interventions.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Twenty-one studies defined normal kidney function by serum creatinine. Non-emergent cardiac surgery was the most commonly reported type of surgery (15 studies, 31%), [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] followed by general surgery (12 studies, 25%), [4,[35][36][37][38][39][40][41][42][43][44][45] vascular surgery (9 studies, 18%), [41,[46][47][48][49][50][51][52][53] orthopaedic surgery (9 studies,18%) [54][55][56][57][58][59][60][61] and urologic/gynaecologic surgery (4 studies, 8%)(62-65). Twenty-two of the 49 studies assessed a single surgical procedure, [24-27, 29, 31-34, 39, 41, PLOS ONE https://doi.org/10.1371/journal.pone.0234402.g001 Thirty six studies did not report dialysis modality, eleven studies specifically examined haemodialysis patients only,…”
Section: Description Of Included Studiesmentioning
confidence: 99%